The Effect of Divided Government and The Incumbent Leader on The Economic Growth in Indonesia - Nairobi, Nairobi; Ambya, Ambya (FEB - Universitas Lampung, 2020)
Purpose:The purpose of this research is to know the effect of the divided government and the incumbent government on the economic growth in regions and cities in Indonesia. Methodology:This research uses 157 regions and cities which had run the regional election in June till August in 2005 as the sample. This is due to the perception of how the regional election had just begun in 2005 while the next and the upcoming election were held in 2010. By far, the data is taken until the end of 2010 to picture the progress of the governmental performance during the period of the leadership of the incumbent leader. Main Findings:As a result, it is found that the incumbent leader has a negative effect on economic growth. This can be seen on the differences between the area with the new leader and the incumbent leader. There are several causes that lead to these results. First, it shows that the voters have not yet evaluated the performance during the leadership period. Second, because the incumbent leader is in the last period of their leadership, they tend to maximize their personal and their group interest, as well as their party, which is resulted to the ignorance of economic growth. Another key finding is that divided government has no effect on economic growth. In Indonesia, the regional leader anticipates the issue of the divided government by doing accommodative politics for the representative member of the regional house (DPRD). Instead of only becoming the checker and balancing power, this action is taken to support all the actions of the regional leader. Thus, it is confirmed that there is no difference between the divided or unified government.